Collaborative Business Process Management Through a Platform Based on Cloud Computing - Cocconi, Diego Alejandro (2018)
With the wide adoption of the Internet, organizations establish collaborative networks to executeCollaborative Business Processes (CBPs). Current approaches to implement Process-AwareInformation Systems (PAISs) for executing CBPs have shortcomings: high costs and complexityof IT infrastructure to deploy the PAISs; poor support for organization autonomy, decentralizedexecution, global view of message exchange, and peer-to-peer interactions; and rigid platformsfor generating and deploying PAISs on-demand according to the CBPs agreed in collaborativenetworks. To overcome these issues, this work proposes a cloud-based platform for the executionof CBPs. The architecture of the platform with the components and interactions between themare described. The architecture enables the generation and deployment on-demand of the PAISsof the organizations required to implement the agreed CBPs, as well as the execution on-demandof these CBPs by fulfilling the above mentioned issues. The platform also provides approachesto deal with elasticity, privacy, and portability concerns.